GOOGLE CLASSROOM OR MOODLE? : UNIVERSITY STUDENT SATISFACTION IN DISTANCE LEARNING COMMUNICATION DURING COVID-19 PANDEMIC - Gunawan Wiradharma (Jurnal Komunikasi dan Bisnis, 2020)
Distance learning is currently very much influenced by communication media. If in the past distance learning was done by module correspondence via postal delivery, now it is done using public internet facilities. Especially in the COVID-19 pandemic, almost all tertiary institutions utilize online learning for their lectures. There are two features that are commonly and commonly used as learning communication tools namely using Moodle and Google Classroom. The researcher uses the value expectation theory which is a derivative of the uses and gratification theory as a guideline for analyzing data and problems found in this study. Discussion Motives will include information, personal identity, integration and social interaction, and entertainment. Satisfaction will be achieved if the motive is fulfilled. The gap between satisfaction sought and satisfaction obtained will indicate differences in the level of satisfaction. The research method used is a comparative survey research. Data collection techniques through questionnaires were given to each of 116 Moodle and Google Classroom feature users in one of the public higher education in Jakarta. The results of this study were 232 PTN students were satisfied after using Moodle and Google Classroom features. Keywords: Motive, Satisfaction, Google Classroom, Moodle.